2007
DOI: 10.1111/j.1463-1318.2007.01295.x
|View full text |Cite
|
Sign up to set email alerts
|

Enterocele repair by abdominal obliteration of the pelvic inlet: long‐term outcome on obstructed defaecation and symptoms of pelvic discomfort

Abstract: Obliteration of the pelvic inlet with a U-shaped Mersilene mesh provides an effective tool for anatomical correction of enteroceles. However, in the long term one of four patients encounters recurrent symptoms of pelvic discomfort. It seems unlikely that enterocele contributes to obstructed defaecation, as evacuation difficulties persist in around three quarters of the patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 24 publications
1
23
0
Order By: Relevance
“…We did not compare the stages of prolapse using different assessment techniques as we have previously published on the accuracy of assessing POPQ points using dynamic 2D-TPUS in females with POP. 19 In our study, we have shown that in keeping with other studies, [21][22][23][24][25] morphological abnormalities that may not be apparent on vaginal examination, can be detected using ultrasound. However, the clinical relevance of these additional diagnoses using PFUS in females without related symptoms has not been previously established.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…We did not compare the stages of prolapse using different assessment techniques as we have previously published on the accuracy of assessing POPQ points using dynamic 2D-TPUS in females with POP. 19 In our study, we have shown that in keeping with other studies, [21][22][23][24][25] morphological abnormalities that may not be apparent on vaginal examination, can be detected using ultrasound. However, the clinical relevance of these additional diagnoses using PFUS in females without related symptoms has not been previously established.…”
Section: Discussionsupporting
confidence: 65%
“…Small bowel peristalsis may help with the identification of structures filling the hernia, and occasionally, intraperitoneal fluid will outline the cul-de-sac. 21 The sonographical definition of a clinically significant cystocele and rectocele has been described; 6,15 however, there is no comparable cut-off value for a clinically significant enterocoele on ultrasound. In our study, none of the females had an isolated enterocoele.…”
Section: Discussionmentioning
confidence: 99%
“…When surgery is aimed at treating either enterocele or rectocele as an isolated lesion, it is unlikely to cure constipation, even when the anatomical disorder is corrected. 5,6,13,24 Occult rectal prolapse on straining is detected in 50 percent of normal subjects 25 but is present in 96 percent of patients with obstructed defecation. 1 However, constipation is relieved in just half of the cases when only prolapse excision is carried out.…”
Section: Discussionmentioning
confidence: 99%
“…1 Constipation recurred in approximately half of patients one to six years after resection rectopexy, transanal prolapsectomy, rectocele repair, or STARR, 2Y5 and obstructed defecation was found in 75 percent of patients after enterocele repair at a median of 85 months of follow-up. 6 Associated functional disorders are likely to affect the outcome of surgery; for example, in a study of transanal rectal prolapsectomy, the success rate dropped from 74 to 26 percent when either anismus or psychoneurosis was present. 3 Obstructed defecation can be seen as an ''iceberg syndrome,'' 1 in which occult conditions (e.g., rectal hyposensation, anxiety, anismus, and enterocele) act as ''underwater rocks'' underlying the evident lesions (e.g., rectocele or mucosal prolapse).…”
mentioning
confidence: 99%
“…awareness of a bulging mass, a bearing-down sensation and pelvic pressure). Also, chronic urge to defecate and feelings of incomplete defecation, occasionally requiring manual expression to complete evacuation, are common complaints, as well as lower abdominal and back pain and incontinence of gas or faeces [1,[7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%